Path planning for constant speed robot - Abdullah @ Idris, Ahmad Takiyuddin (2006)
The purpose of this thesis is initially to present an implementation of a guidance algorithm based on the geometrical analysis for the adoption of path planning problem. A mobile robot (named toward its unique characteristic in this project as constant speed robot) moving at a constant speed and having a constant swerving ability is used in the analysis. The guidance algorithm is formed based on an initial direction and distance of the target location without considering the time taken by the robot to reach the desired destination. At the moment, the guidance algorithm managed to assist the robot to reach the desired destination, within a certain small error tolerance. The development of the path planning algorithm is initially presented by the geometrical analysis and it is then analyzed by simulation using Matlab. The simulation analysis is performed to prove the effectiveness and robustness of the guidance algorithm for the mobile robot. The performance of the guidance algorithm will be compared with an existing guidance algorithm based on kinematics geometry introduced by Lin [5] and with an alternative guidance strategy employing geometrical analysis and Matlab’s simulation